Radiation Dosimetry in Non-Hodgkin’s B-Cell Lymphoma Patients Treated with 131I-Rituximab Radioimmunotherapy - Wirote Changmuang (2022)
Objective: The aim of this study was to calculate a therapeutic dose of 131I-Rituximab after a tracer patient-specific dosimetry based on whole body absorbed dose of 0.75 Gy. Methods: Eight patients (mean ± S.D. age, 59.0 ± 11.6 years) were given initial tracer activity of 131I-Rituximab intravenously. Whole body images at 10 minutes, 3 days and 6 days were used to generate the Time-activity curve (TAC). TAC was fitted by plotting Log10 of the percentage administered activity remaining with time of scan and was used for calculation of the effective half-life, residence time and therapeutic dose. The organs dose was calculated by MIRDOSE 3.1 software. Results: The mean effective half-life was 145.7 ± 13.4 hours, whereas the residence time was 210.3 ± 19.4 hours. The mean therapeutic dose was 1.16 ± 0.16 GBq. The mean absorbed dose to liver, lungs, ovaries, red marrow, testes and total body was 0.58 ± 0.05, 0.54 ± 0.05, 0.63 ± 0.06, 0.56 ± 0.05, 0.53 ± 0.05 and 0.54 ± 0.06 mGy/MBq, respectively. Conclusions: The whole body radiation dose using a patient-specific tracer dose calculation based on whole body absorbed dose of 0.75 Gy was appropriate for therapeutic dose calculation in Radioimmunotherapy (RIT) patient.